Gendering Technological Change: Evidence from Agricultural Mechanization - Farzana Afridi; Monisankar Bishnu; Kanika Mahajan (Institute of Labor Economics (IZA), 2020)
Technological change in production processes with gendered division of labor across tasks, such as agriculture, can have a differential impact on women's and men's labor. Using exogenous variation in the extent of loamy soil, which is more amenable to deep tillage than clayey soil and therefore more likely to see adoption of tractor driven equipment for primary tilling, we show that mechanization has led to significantly greater decline in women's than men's labor on Indian farms. Reduced demand for labor in weeding, a task that requires precision and is thus more often undertaken by women, explains our findings. The estimates suggest that increased mechanized tilling led to a more than 22% fall in women's agricultural labor in India during 1999-2011. Our results highlight the gendered impact of technological change in contexts where there is sex-specific specialization of labor.
Keywords: J16; J23; J43; O33; 330; gender; specialization of labor; agriculture; technology; mechanization